Livelihood Assessment of Fishers in Dal Lake, Kashmir (Indian Journal of Extension Education, 2023)
The study investigates the livelihood conditions, vulnerability, and resilience of the Dal Lake fishers and their readiness and strength to withstand climate shocks and vulnerabilities. The study was conducted in 2019-2020 in three fishing villages of Dal Lake Kashmir, where the livelihood and vulnerability of fisheries-based livelihoods were assessed through a composite index development approach. The fishers of Dal Lake are moderately vulnerable to climate variability and changes. The status of the livelihood capitals of the fishers reveals that most of the capitals are of moderate type, however, the financial capital is poor horizontally among all the fishing villages. It was also found that the socio economic conditions and resilience of the people are in very poor condition. The fisheries related activities and policies are being side-lined because of giving more importance to tourism. The management of the lake is shared between the Fisheries & Tourism departments, and the Jammu and Kashmir Lakes Conservation and Management Authority (power). However, lack of coordination, less availability of resources, less priority to the fisheries sector, and lack of accountability hindered the desired outcomes. Proper management of the lake, coordination between the key stakeholders and fishers is very important and can be achieved through network governance.